Pengaruh Stres Kerja dan Kompensasi Terhadap Turnover Intention Melalui Kepuasan Kerja Sebagai Variabel Intervening Di Unit KCU Kopi Jakarta Barat - Wulandari, Evvie Ariantya; Prahiawan, Wawan (Faculty of Economics and Business - Universitas Sultan Ageng Tirtaysa, 2019)
The purpose of this study was to analyze the effect of work stres through job satisfaction on KCP employee turnover intention Panin Bank in KCU Coffee Unit; to analyze the effect of compensation through job satisfaction on KCP employee turnover intention Panin Bank in KCU Coffee Unit and to analyze the influence of job satisfaction on KCP employee turnover intention Panin Bank in KCU Kopi Unit.The research method used is quantitative with an explanatory survey research approach or correlational design through data collection techniques using questionnaires. The population is all employees at KCP Panin Bank in KCU Coffee Unit West Jakarta totaling 206 people with a sample of more than 20%, amounting to 98 people. Data analysis techniques are used using path analysis using PLS.The results showed that work stres had a positive effect on turnover intention, compensation had a negative effect on turnover intention, work stres had a negative effect on job satisfaction, compensation had a positive effect on job satisfaction and job satisfaction had a negative effect on turnover intention.